Introducing Governance as Foundation for Self-Development: Community Service at SMAK BPK Penabur - Zubaedah, Siti Yasmina; Hartono, Rudi (Universitas Serang Raya, 2026)
The community service conducted at SMAK BPK Penabur Sentul, on January 31, 2025, was in conjunction with the self-development program included in the high school’s curriculum and part of maintaining the students’ well-being at school. Implementing good governance starts with the individuals who are members of the organization, each practicing self-regulation. Based on the survey, all components obtained a score of above three, which indicated that the students perceived an overall positive experience. The workshop reported in this article exemplifies the value of such community service for the collaborating high school and university, as well as for all individuals involved. Ultimately, this community service format offers a distinct learning experience for high school students and can also enhance university-level lecturers' teaching skills.